Extensor Pollicis Longus Rupture after Mini TightRope Suspensionplasty - Seetharaman, Mani; Vitale, Mark A.; Desai, Kapil; Crowe, John F. (Journal of Wrist Surgery, 2016)
Background Arthritis of the first carpometacarpal (CMC) joint has been surgically treated in multiple ways with varying levels of success as measured by subjective and objective measures. Trapeziectomy with numerous variations in suspensionplasty comprises one of the more commonly used surgical procedures. Recently, the Mini TightRope apparatus has been utilized as a new method for achieving suspensionplasty, and as such lacks significant review of use and safety in the literature.Case Description An extensor pollicis longus (EPL) rupture following a trapeziectomy and Mini TightRope suspensionplasty for CMC arthritis of the thumb is presented. The patient successfully underwent an extensor indicis proprius (EIP) to EPL transfer to treat this complication.Literature Review There is well-established documentation of injury to the extensor tendons from orthopedic hardware such as volar locking plates. Regarding use of the Mini TightRope apparatus, guidelines for placement of the suture button include caution to place the button away from the EPL tendon to minimize the chance of tendon irritation. Additionally, FiberWire sutures, a component of the apparatus, have been shown to demonstrate soft tissue reactions with adjacent inflammatory response. Published reports on adverse events utilizing this device have been limited to case reports including an index metacarpal fracture.Clinical Relevance The aim of this case report was to cite an occurrence of EPL rupture following its use and discuss the possibilities of its direct contribution.
Keywords: EPL rupture; Mini TightRope; suspensionplasty; trapeziectomy